A COMPARISON OF LEUPROLIDE ACETATE VERSUS BILATERAL ORCHIECTOMY FOR PATIENTS WITH METASTATIC PROSTATE CANCER - Purushothaman, Aiswarya; Kumar, Ginil; P, Gangadharan; PR, Roshni (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Prostate cancer is the most common visceral malignancy and leading cause of cancer‑related death in men. Androgen deprivation therapy is the established treatment of metastatic prostate cancer and has different approaches in the reduction of androgen activity including surgical castration (bilateral orchiectomy) and medical castration (luteinizing hormone‑releasing hormone agonists/antagonists). Our purpose was to study the clinical profile, effectiveness, and outcome of South Indian patients with metastatic prostate cancer undergoing treatment with surgical and medical castration. Methods: A total of 30 surgical and 30 medical castration patients diagnosed with metastatic prostate cancer between (2008 and 2009) were followed up to 5 years. Serum prostate specific antigen (PSA) levels at the time of the first diagnosis, post‑treatment nadir PSA levels, time to nadir PSA, time to hormonal resistance between the study groups were assessed, retrospectively. The Kaplan–Meier method was used with log‑rank test for survival rate calculations. Gleason score, PSA levels, skeletal‑related events, and sites of metastasis of the study groups were studied. Result: The average survival time after medical castration was 60 months and 42 months for surgical castration. No significant difference could be established between the groups. Bone was the most common site of metastasis and radiation was the major skeletal‑related events in medical groups. Conclusion: There were no statistical differences between the groups in terms of treatment modalities in metastatic prostate cancer. Keywords: ???